An artificial piezotronic synapse for tactile perception - Kumar, Mohit; Singh, Ranveer; Kang, Hyunwoo; Kim, Sangwan; Seo, Hyungtak (Nano Energy, 2020)
Intelligent neuromorphic tactile perception architecture requires the integration of pressure sensors, connecting cables, and artificial synapses, which poses serious challenges to complex device integration and overall energy consumption. Therefore, the development of self-adaptive, high performance and sophisticated artificial synapses with an uncomplicated fabrication process that can adjust its output with the tactile environment is essential. Here, we developed a proof-of-concept simple two-terminal, highly transparent, and flexible piezotronic artificial synapse that emulates environment-adaptable tactile perception. Specifically, all typical synaptic functions, such as excitation/depression, plasticity, and paired-pulse facilitation, are sensitive to the applied strain, thus providing artificial in-situ “touch sensing”. The observed effect is attributed to the dynamic charge trapping/detraining via strain-modulated band alignment and is qualitatively confirmed by Kelvin probe force microscopy measurements. The presented work provides new insights into simplifying the circuitry of neuromorphic tactile perception, resulting in a number of additional applications toward skin‐attachable electronics, robotics, and prosthetics.
Keywords: Artificial synapse; Band alignments; Complex devices; Dynamic charges; Fabrication process; Kelvin probe force microscopy; Proof of concept; Tactile perception; Artificial synapse; Flexible; Highly transparent; Piezotronic; Tactile perception